Multimobile Development: Building Applications for the iPhone and Android Platforms - Baxter-Reynolds, Matthew (Apress, 2012)
For me, this book has become all about change. In the time that I have been watching the mobile computing marketplace and developing software solutions for it, there has never been a time when there has been a more rapid series of shifts and changes. A good friend of mine tells me that this is because of market consolidation. As of the time of writing (August 2010), we’re looking at the time when the people who will be leaders in this space for the next 20 years jostle for position. There is a ton of money out there being spent, which is fantastic news for the typical reader of this book. Position yourself correctly and you could earn a seriously good living out of it all. . To illustrate this point about change, I proposed this book to Apress in February 2010, and in just half a year between then and August 2010, here are just some of the changes that have happened. In a normal year, in a normal market, just a few of these things would be big news.